1996
DOI: 10.2166/wst.1996.0327
|View full text |Cite
|
Sign up to set email alerts
|

Design and operations experience with flocculator-clarifiers in large plants

Abstract: Historically, secondary clarifiers have contributed to instability in plant performance. The flocculator-clarifier development has demonstrated in a variety of plant situations that stable secondary process operation is achievable. Consistently low effluent SS levels (average values of 10 mg/l) are realistically achievable. This performance enhancement has been obtained at lower costs than for conventional designs. The clarifier incorporates some special design features including a large flocculator centerwell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…And a comprehensive evaluation of the flocculation and breakup kinetics of a large number of conventional activated sludge plants allowed confirmation of standardized flocculation zone residence times (Wahlberg et al,1994). Computational fluid dynamics modeling and field testing allowed simultaneous optimization of flocculator center well diameter and depth, sidewater depth and effluent launder position, as described in a paper describing the history of the flocculator clarifier development (Parker et al, 1996). Typical features of the flocculator clarifier, as designed by Brown and Caldwell, are shown in Figure 6.…”
Section: The Flocculator Clarifiermentioning
confidence: 99%
“…And a comprehensive evaluation of the flocculation and breakup kinetics of a large number of conventional activated sludge plants allowed confirmation of standardized flocculation zone residence times (Wahlberg et al,1994). Computational fluid dynamics modeling and field testing allowed simultaneous optimization of flocculator center well diameter and depth, sidewater depth and effluent launder position, as described in a paper describing the history of the flocculator clarifier development (Parker et al, 1996). Typical features of the flocculator clarifier, as designed by Brown and Caldwell, are shown in Figure 6.…”
Section: The Flocculator Clarifiermentioning
confidence: 99%
“…1 showed that it could be used for nitrification of ammonia laden filtrate from solids processing, while reducing the SRT that would otherwise to sustain nitrification down to the lowest temperatures anticipated (10 o C). High rate clarifiers were constructed to allow for the high peak wet weather flows (Parker et al, 1996). Table 2 shows the design criteria for the activated sludge portion of the plant, while Table 3 shows typical operating data.…”
Section: Figure 2 -The Bar Processmentioning
confidence: 99%
“…This way of denitrification may benefit the treatment of wastewater since organic substrates and ammonia are simultaneously oxidized during conventional treatment, which results in a shortage of the organic substrate needed for subsequent denitrification. Results of other studies postulated that, because of the competition between heterotrophic bacteria and nitrifiers, nitrification is not initiated until the soluble COD drops to less than 27 mg/ l or the soluble BOD 5 drops to 20 mg/l [18,19].…”
Section: Nitrogen Removalmentioning
confidence: 99%